2023
DOI: 10.3389/fspor.2023.1147384
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical activity on glutamate neurotransmission in neuropsychiatric disorders

Abstract: Physical activity (PA) is an effective way of increasing cognitive and emotional health and counteracting many psychiatric conditions. Numerous neurobiological models for depression have emerged in the past 30 years but many struggle to incorporate the effects of exercise. The hippocampus and pre-frontal cortex (PFC) containing predominantly glutamate neurotransmission, are the centres of changes seen in depression. There is therefore increasing interest in glutamatergic systems which offers new paradigms of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 165 publications
0
2
0
Order By: Relevance
“…Nowadays, it is completely accepted that physical activity is an effective way to increase cognitive and emotional health in many psychiatric conditions. In particular, several studies have demonstrated that physical activity significantly improved brain function, counteracting the negative effects of aging on cognitive performance and reducing the risk of dementia [ 162 ]. Interestingly, it was suggested that physical activity in humans correlates with the gut microbiome, which could prevent the incidence and development of Alzheimer’s disease [ 163 ].…”
Section: Environmental Enrichmentmentioning
confidence: 99%
“…Nowadays, it is completely accepted that physical activity is an effective way to increase cognitive and emotional health in many psychiatric conditions. In particular, several studies have demonstrated that physical activity significantly improved brain function, counteracting the negative effects of aging on cognitive performance and reducing the risk of dementia [ 162 ]. Interestingly, it was suggested that physical activity in humans correlates with the gut microbiome, which could prevent the incidence and development of Alzheimer’s disease [ 163 ].…”
Section: Environmental Enrichmentmentioning
confidence: 99%
“…It would be intriguing to investigate the association between increased vigorous PA in ASD patients compared with TD children and unbalanced excitatory/inhibitory neurotransmission, oxidative stress, and neuroinflammation as ASD etiological processes related to hyperactivity [44,45]. Individuals with autism have substantially greater glutamate, the primary excitatory neurotransmitter, and much lower gamma amino butyric acid (GABA), the primary inhibitory neurotransmitter [6,46].…”
Section: Vigorous Pa In Asd Patientsmentioning
confidence: 99%